CYP2D6 GENOTYPE AND PLASMA CONCENTRATIONS OF OLANZAPINE - IMPORTANCE FOR SAFETY IN BIOEQUIVALENCE STUDIES - Jakjovski, Krume; Kapedanovska Nestorovska, Aleksandra; Trojachanec, Jasmina; Atanasovska, Emilija; Kostova, Elena; Labachevski, Nikola (Македонско лекарско друштво = Macedonian medical association, 2013)
Introduction. Functional status of izozymes CYP2D6 and CYP1A2 has a major impact on pharmacokinetics of a number of psychotropic drugs. There are no definitive data on the predictive role of these enzymes. Our goal was to show, in our conditions, whether the disposition of olanzapine is associated with the impact of polymorphisms of CYP2D6 by deductive comparing the pharmacokinetic results of a bioavailability study. Methods. Blood samples were taken from healthy subjects participating in studies of bioavailability, for genotyping for the most common polymorphic allelic variants. Gene duplication genotyping was performed at the Faculty of Pharmacy using PCR technique. Concentrations of olanzapine in plasma were assessed with appropriate HPLC method. Results. The most common allelic variants of CYP2D6 and their frequency were determined; subsequently 4 groups of phenotypes (EM, IM, PM and UM) were promoted. For 14 subjects divided into 3 groups of phenotypes Cmax, AUC0-t and AUC0-inf were determined. Despite the apparent numerical differences in concentrations of maximum plasma concentrations and the area under the curve, there were no significant difference between the groups (EM: IM, EM: UM). Adverse reactions were mild by nature and were expected for the drug: headaches and dry mouth, which are typical for antipsychotic drugs, especially for olanzapine at a dosage of 10 mg. Conclusions. Additional research has to be made to confirm the impact of CYP2D6 allelic gene variants on the pharmacokinetics of olanzapine. In future studies of bioavailability, subjects with a certain phenotype must be assesed with caution due to the potential possibility of increased drug concentrations.
Keywords: CYP2D6; olanzapine; allelic variants; bioequivalence